2011
DOI: 10.4103/0973-6247.75979
|View full text |Cite
|
Sign up to set email alerts
|

Serial follow-up of repeat voluntary blood donors reactive for anti-HCV ELISA

Abstract: Background:Voluntary non-remunerated repeat blood donors are perceived to be safer than the first time blood donors. This study was planned for follow-up of previous hepatitis C virus (HCV) test results of anti-HCV enzyme-linked immunosorbent assay (ELISA) reactive repeat blood donors. The aim was to suggest a protocol for re-entry of the blood donors who are confirmed HCV negative by nucleic acid test (NAT) and recombinant immunoblot assay (RIBA). A group of repeat voluntary donors were followed retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Indeed, 41% of initially reactive samples which could be analyzed were not reproduced when retested with the same reagent. Repeat testing is known to improve specificity (Choudhury et al, 2011; Piro et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, 41% of initially reactive samples which could be analyzed were not reproduced when retested with the same reagent. Repeat testing is known to improve specificity (Choudhury et al, 2011; Piro et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Several solutions have been proposed. One could test simultaneously with two assays and exclude donors reactive with both since these subjects have the highest probability to be positive with NAT and/or Immunoblot (Choudhury et al, 2011). Nevertheless, two tests increase the cost of the screening unless a sequential screening strategy is used (Seed et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in different population groups found varying prevalence rates [ Table 1 ]. [ 10 11 12 13 14 15 16 17 18 19 ]…”
Section: Epidemiology Of Hcv Infectionmentioning
confidence: 99%
“…The low detection rate could be generally interpreted by different dynamics of antibody and viral nucleic acid, such as spontaneous clearance of HCV or resolved HCV RNA in blood specimens (20)(21)(22)(23). However, no partial sequence was amplified in the specimens negative for anti-HCV while positive by NAT.…”
Section: Discussionmentioning
confidence: 99%